Penerapan Model Pembelajaran Project Based Learning (PjBL) dalam Meningktkan Keterampilan Berpikir Kritis Siswa Kelas X MIA 1 SMA Negeri 2 Sirenja Pada Pelajaran Biologi - Safarni, Safarni; Shamdas, Gamar B.N.; Windarsih, Yulia; Jamhari, Mohammad; Lilies, Lilies; Astija, Astija (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to improve the critical thinking skills of class X MIA 1 students at SMAN 2 Sirenja through the implementation of the Project Based Learning (PjBL) model in Biology subjects. This research used a Classroom Action Research (CAR) approach, conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through teacher and student activity observations, as well as critical thinking skill tests. Research data were analyzed using descriptive statistics. The results showed a significant improvement from cycle I to cycle II. Classical completeness increased from 41.17% to 88.2%, while classical absorption increased from 64.26% to 80.8%. Both teacher and student activities improved, reflecting higher engagement in the learning process. In addition, critical thinking indicators such as analysis, evaluation, and problem-solving showed positive development.Thus, the implementation of the Project Based Learning model proved effective in enhancing students' critical thinking skills and in creating a more active, collaborative, and contextual learning environment.Â